SKIKDA CITY DIMENSIONS OF URBAN DEVELOPMENT IN THE LAND OCCUPATION PLAN FOR THE SOUTH OF SKIKDA CITY (SECTION 2) - Boucherma Nadjet, (International Journal of Innovative Technologies in Social Science, 2024)
The city of Skikda has been an attractive area for rural residents of the countryside and neighboring and distant communes, because of the job opportunities it offers due to the presence of the commercial port, especially when the industrial zone was established, which caused the emergence of several urban issues, the most important of which are: The lack of housing and equipment, the spread of unemployment, the rapid and chaotic expansion of the city center due to urban growth and rural migration, the saturation of the city area, and the need to search for areas for its expansion. The study area considers the future expansion of the city of Skikda in the southern part through the land occupation plan for the south of the city of Skikda city (section 2) as a tool for urban planning, as it programmed housing projects to cover the housing deficit in the city, equipment and technical networks to ensure social services and economic functions and to protect and improve the environment of buildings and the urban environment, all for the benefit of the population to improve their standard of living and maintain their stability, all within the framework of the urban development of Skikda city.